Medicare Outpatient Physical Therapy Expenditures Vary by Diagnosis and Functional Mobility. Issue 5 (25th February 2019) - Pardasaney, Poonam K; Pope, Gregory C; Amico, Peter; Deutsch, Anne; Kline, Tracy; Dever, Jill; Silver, Benjamin; Scheffler, Scott; Meadow, Ann; West, Pamela
Abstract: Background: Clinical characteristics driving variations in Medicare outpatient physical therapy expenditures are inadequately understood. Objective: The objectives of this study were to examine variations in annual outpatient physical therapy expenditures of Medicare fee-for-service beneficiaries by primary diagnosis and baseline functional mobility, and to assess whether case mix groups based on primary diagnosis and functional mobility scores would be useful for expenditure differentiation. Design: This was an observational, longitudinal study. Methods: Volunteer providers in community settings participated in data collection with Continuity Assessment Record and Evaluation—Community (CARE-C) assessments for Medicare fee-for-service beneficiaries. Annual outpatient physical therapy expenditures were calculated using allowed charges on Medicare claims; primary diagnosis and baseline functional mobility were obtained from CARE-C assessments. Whether annual expenditures varied significantly across primary diagnosis groups and within diagnosis groups by functional mobility was examined. Results: Data for 4210 patients (mean [SD] age = 72.9 [9.9] years; 64.6% women) from 127 providers were included. Mean expenditures differed significantly across 12 primary diagnosis groups created from CARE-C clinician-reported diagnoses ( F = 12.73; df = 11). Twenty-five pairwise differences in 66 pairwise diagnosis group comparisons were statistically significant. Within 8 diagnosis groups, expenditures were significantly higher for low-mobility subgroups than for high-mobility subgroups; borderline significance was achieved for 1 diagnosis group. Limitations: The small convenience sample limited the statistical power and the generalizability of the results. Conclusions: Significant variations in physical therapy expenditures based on primary diagnosis and baseline functional mobility support the use of these variables in predicting outpatient physical therapy expenditures. Although Medicare's annual therapy spending cap was repealed effective January 2018, the data from this study provide an initial foundation to inform any future policy efforts, such as targeted medical review, risk-adjusted therapy payments, or case mix groups as potential payment alternatives. Additional research with larger samples is needed to further develop and test case mix groups and improve generalizability to the national population. Refined case mix groups could also help providers prognosticate physical therapy expenditures based on patient profiles.